Identification of Coliform bacteria content in ‘Thai Tea' drinks and its correlation with hygiene factors in Yogyakarta, Indonesia - Dyah Suryani; Sunarti Sunarti; Rosyida Awali Safitri; Hesti Khofifah; Suyitno suyitno (Public Health of Indonesia)
Background: Various water-borne diseases have been seen in developed and developing countries, like  Coliform bacteria in food and drink due to their poor making.